Complete resolution of the giant pulmonary bulla: a case of inflammatory autobullectomy - Sungrock Park; Hyejin Shi; Sungho Wang; Sangki Lee; Yousang Ko; Yong Bum Park (Kosin Medical Journal, 2018)
Giant pulmonary bulla (GPB) is a rare manifestation of emphysema and usually enlarges gradually over time, occasionally resulting in complications. Hence, more often than not, the surgical intervention of a Bullectomy is the standard method of treatment for GPB. However, there are case reports that show the complete resolution of GPB after its inflammation process even without surgical intervention. A 51-year-old man was admitted to our clinic due to pleuritic pain. After a chest X-ray and CT scan, a new air-fluid level within the GPB was revealed in the right upper lobe of his lung. His clinical status had improved promptly with intravenous antibiotics. A one-year follow-up study showed the GPB was completely resolved.